1997
DOI: 10.1074/jbc.272.6.3384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amino Acid Substitutions on the Activity of Carnobacteriocin B2

Abstract: Carnobacteriocin B2, a 48-amino acid antimicrobial peptide containing a YGNGV motif that is produced by the lactic acid bacterium Carnobacterium piscicola LV17B, was overexpressed as fusion with maltose-binding protein in Escherichia coli. This fusion protein was cleaved with Factor Xa to allow isolation of the mature bacteriocin that was identical in all respects to that obtained from C. piscicola. Similar methodology permitted production of the precursor precarnobacteriocin B2 (CbnB2P), which has an 18-amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
53
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 31 publications
1
53
0
Order By: Relevance
“…These peptides are usually basic and between 30 and 60 residues long. The production of bacteriocins is, at least in some strains, controlled by a quorum sensing mechanism that involves a secreted peptide pheromone with bacteriocin-like characteristics (3)(4)(5)(6)(7). Like bacteriocins, these peptide pheromones are cationic and they are exported from the cell with help of a bacteriocin-type leader peptide and secretion machinery.…”
mentioning
confidence: 99%
“…These peptides are usually basic and between 30 and 60 residues long. The production of bacteriocins is, at least in some strains, controlled by a quorum sensing mechanism that involves a secreted peptide pheromone with bacteriocin-like characteristics (3)(4)(5)(6)(7). Like bacteriocins, these peptide pheromones are cationic and they are exported from the cell with help of a bacteriocin-type leader peptide and secretion machinery.…”
mentioning
confidence: 99%
“…The main effect of peptide 2 would be the increase in bacteriocin killing rate. Because this domain would be involved in the initial unspecific binding with the membrane and would not be related to pore formation (5,17), a plausible explanation might be that the first interaction of peptide 2 with the membrane would facilitate later binding and correct insertion of enterocin CRL35.…”
mentioning
confidence: 99%
“…Furthermore, studies of the C-terminal 15-mer region of pediocin PA-1 revealed that the fragment interfered with the inhibitory activity of the native peptide (15). More recent studies have investigated multiple mutants with mutations at different residues (30,33,36). Six mutants with mutations at 6 different residues of carnobacteriocin B2 (36), 10 with mutations at 8 different residues of mesentericin Y105 (33), and 17 with mutations at 14 different residues of pediocin PA-1 (30) were generated by random PCR mutagenesis.…”
mentioning
confidence: 99%